(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
During the research, it was found that when sowing seeds on October 20, the number of surviving plants will be 475-550, the degree of preservation is 80-82% when planting at the rate of 8-10 million seeds, and 81% when planting at the rate of 12 million seeds. When analyzing the safety of Ryzhik varieties at the end of the growing season, it was found that although there was no sharp difference between varieties and planting dates, planting rates had an impact. The highest rate of plant safety is 78-80% in the variants with sowing 8-10 million seeds, and the lowest is 76% in the variant with sowing 12 million seeds. The feeding area is reduced.